SELECTIVE AMPLIFICATION OF CATECHOL 2, 3 DIOXYGENASE GENE FROM HENOL DEGRADING ALCALIGENES SP D2 ISOLATED FROM SOIL - ASHIQ.M,; INDU C NAIR,; SAJUDEEN.P.A,; JAYACHANDRAN.K., (International Journal of Pharma and Bio Sciences, 2013)
Catechol 2, 3-Dioxygenase transforms catechol by meta cleavage to 2-hydroxymuconate semialdehyde. The meta pathway is functional in the microbial degradation of phenol and many such organic compounds. In the present study an attempt was made to isolate and purify catechol 2, 3- dioxygenase from a phenol degrading Alcaligenes sp d2. The enzyme in the culture extract was precipitated at 80% ammonium sulphate concentration and was dialysed overnight. The dialysed fraction was subjected to gel filtration using Sephadex G-100 using phosphate buffer of 50mM concentration and pH 7.5. The three fractions with an elution volume of 7.5ml carrying the enzyme were pooled, concentrated and the purity of the enzyme fraction was confirmed by PAGE. An attempt was also made to selectively amplify the gene encoding catechol 2,3 dioxygenase. The amplified product appeared in the Agarose gel was corresponding to a molecular weight of 200bp.